Handgrip strength of Colombian university students (2016)
Introduction: Handgrip strength (HGS), evaluated with a handgrip dynamometer, is a marker of current nutritional status and cardiometabolic risk, as well as of future morbidity and mortality. Objectives: We present reference values for HGS of Colombian university students. Methods: Cross-sectional study. The sample comprised a number of students (n = 5,647, 58.5% women) who were apparently healthy (mean age, 20.6 ± 2.7 years) attending public and private institutions in the cities of Bogota and Cali (Colombia). HGS was measured using a manual dynamometer, adjusted for each individual according to hand size. Sex- and age-specific normative values for HGS were calculated using the LMS method and expressed as tabulated percentiles from 3 to 97 and as smoothed centile curves (P3, P10, P25, P50, P75, P90 and P97). Results: The mean HGS value was significantly higher in men (37.1 ± 8.3 kg) when compared to women (24.2 ± 8.1 kg) (p < 0.001). HGS increased with age in both sexes and was significantly higher for men in all age categories. The results were generally more homogeneous among men than women. Sex- and age-specific handgrip strength normative values among healthy young Colombian adults are defined. Conclusion: This information may be helpful in future studies of secular trends in HGS and in identifying clinically relevant cut points for poor nutritional and elevated cardiometabolic risk in a Latin American population. Evidence of a decline in HGS before the end of the third decade of life is of concern and warrants further investigation. © 2016, Grupo Aula Medica S.A. All rights reserved.